Gypsum stabilization for enhancing the compressive behavior of rammed earth: experimental and statistical assessment - Ávila, Fernando; Fagone, Mario; Gallego, Rafael; Puertas, Esther; Ranocchiai, Giovanna (Frontiers in Built Environment, 2025)
Gypsum has historically been used as an additive in rammed earth construction to enhance its mechanical properties. However, its application has declined in modern practice, and scientific literature on gypsum-stabilized rammed earth remains limited. This study investigates the effectiveness of gypsum as a stabilizer to improve the compressive behavior of rammed earth, presenting it as a sustainable alternative to Portland cement, which, despite its widespread use, entails higher environmental and economic costs. To assess the influence of gypsum, uniaxial compression tests were performed on rammed earth specimens with varying gypsum contents (0%–15%). The results demonstrate significant increases in compressive strength (up to 130%) and elastic modulus (up to 262%) with gypsum inclusion, with the highest values recorded for the 15% gypsum-stabilized mixture (3.2 MPa and 267 MPa, respectively). Statistical analysis, including analysis of variance (ANOVA), confirmed the significance of these enhancements, with only the difference in elastic modulus between the 10% and 15% mixtures showing no statistical significance. These findings highlight gypsum as a viable eco-friendly solution for improving the mechanical performance of rammed earth construction.